COMPETITIVENESS OF BUSINESS STRUCTURES IN THE INNOVATION ENVIRONMENT AND DEFINITION OF THE CONCEPT OF «INNOVATION FORESIGHT» SYSTEMATIC APPROACH - Mukhamedkhanova A. B.; Tulemetova A. S.; Zhurynov G. M. (Scientific Journal of Pedagogy and Economics, 2021)
The problems of ensuring effective management and forming competitiveness of industrial enterprises are relevant regardless of the conditions for conducting business activities. The fact is that the competitiveness of business structures in modern conditions is not ensured by simply owning factors of production (labor, capital, land), and even entrepreneurial talent is not currently a source of obtaining stable or exclusive competitive advantages. In order to obtain sustainable or exclusive competitive advantages that constitute strategic competitiveness, the business structure needs to have an intellectual (educational) component of development, including the production and implementation of innovations, as well as readiness for changes. Subject of research. On the basis of innovative foresight, ensuring the competitiveness of business structures of the production industry is a set of organizational, managerial and economic relations that arise in the process of formation. Purpose and objectives of the study. Development of proposals to improve the competitiveness of business structures based on innovative foresight. A number of theoretical, methodological and practical issues related to the formation and implementation of a strategy for managing the innovative development of entrepreneurial structures based on innovative foresight remain insufficiently studied and require further development of rules for its creation and functioning. At the same time, despite a detailed description of the problems of strategic management of innovative development of business structures, the research of foreign scientists was carried out in relation to the relatively stable conditions of the economy of developed countries, the practical application of the mechanisms proposed by them in the conditions of the Kazakh economy requires mandatory revision, taking into account the specifics of the modern economy and industry.